Case Report: Breast ductal carcinoma in situ with microinvasion: a case tracked over 13 years - Ruan, Sibei; Zhou, Jian; Tang, Rui; Wang, Tao; Gao, Xia; Mou, Lixian; Tang, Mingxi (Frontiers in Oncology, 2025)
BackgroundNumerous studies have reported considerable heterogeneity in breast ductal carcinoma in situ with microinvasion (DCIS-MI) regarding clinical presentation, progression potential, and treatment strategies.Case presentationIn this work, we report a case of rapidly progressing multiple metastases in a patient with DCIS-MI following conventional treatment. Subsequent fluorescence in situ hybridization (FISH) testing revealed HER2 gene overexpression. After receiving 10 cycles of trastuzumab-targeted therapy, the patient achieved a favorable prognosis and remains stable to date.ConclusionThis case suggests that even patients with microinvasive lesions who are HER2-positive may exhibit unexpected stability under targeted therapy, warranting close surveillance in such cases.